Inovasi Strategis : Alternatif Keputusan Keuangan Syariah untuk Percepatan Pembangunan Daerah Tertinggal - Pramesti, Angeline Wita (Business Finance Analyst Co., 2024)
This research aims to investigate alternative decisions in spending, financing, and investment in Islamic finance as well as the research contribution to accelerating the development of rural, coastal, and underdeveloped areas. The research methodology used is descriptive analysis by collecting data from various related literature sources. The results of the research show significant potential in implementing Islamic finance as a sustainable and ethical alternative in economic development in remote areas. Sharia-compliant investment management also plays a crucial role in enhancing the competitiveness of local products through digital marketing. Furthermore, innovative Sharia-compliant financing models can also make a significant contribution to infrastructure and local economic development. The findings of this research provide practical implications relevant to decision-makers in the field of Islamic finance and lay the groundwork for further research in supporting sustainable development in marginalized areas .